Clinical course of disseminated Kaposi sarcoma in a HIV and hepatitis B co-infected heterosexual male - Manoj Kumar Agarwala; Renu George; Thambu David Sudarsanam; Raju Titus Chacko; Meera Thomas; Sheila Nair (Wolters Kluwer Medknow Publications, 2015)
AIDS associated Kaposi sarcoma (AIDS-KS) was first reported from India in 1993. Since then only 16 cases have been reported. Three of them had proven Human Herpesvirus 8 (HHV-8) infection. We report a case of disseminated KS in a heterosexual male from India with HIV, hepatitis B and HHV-8 infection. He was given six cycles of chemotherapy with liposomal doxorubicin over three months to which he showed a good response. The case highlights the clinical course and management of a HHV-8 positive disseminated KS in a patient co-infected with Hepatitis B and HIV.